Tensions and directions of internationalization in Brazil: Between competition and solidarity - Finardi, Kyria Rebeca; Macêdo Mendes, Ana Rachel; Aparecido da Silva, Kleber (Education Policy Analysis Archives, 2022)
The article discusses some issues related to perceived tensions between the forces/trends of competition and solidarity in the internationalization of higher education in Brazil. With this aim, the article reviews two of the largest Brazilian programs of academic mobility as evidence of internationalization policies for higher education: the academic mobility program to send academics abroad – Science without Borders (SwB) – and the Graduation Student Program (PEC-G) of academic mobility to Brazil. These two programs are analyzed in relation to the evidence of competition (in the case of SwB) and solidarity (in the case of the PEC-G). Overall, the study concludes the scale of internationalization in Brazil is still pending more towards competition than towards solidarity.